IMPLEMENTASI PROBLEM BASED LEARNING MAHASISWA AKUNTANSI KEUANGAN POLITEKNIK NEGERI MANADO - Wenny Anggeresia Ginting; Shane Anneke Pangemanan; Reski Amalia; Ficky Marchfirmanto (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2024)
Problem Based Learning (PBL) is a learning model that is thought to be suitable to be applied in the learning process to improve learning outcomes while honing the ability to think about a problem to be solved critically through the stages of the scientific method. This study aims to analyze the learning outcomes of accounting students in the Bachelor of Applied Financial Accounting Study Program of Manado State Polytechnic through the application of the PBL model. This research is a quantitative study with a quasi-experimental method, namely by comparing the experimental class that uses the PBL model and the control class that does not use the PBL model. The population in this study was 133 semester 4 students while the sample was 65 people. The sampling technique uses cluster sampling. The results of the study were through a t-test with a value of tcount = 3.88 and ttable = 1.999, so that H1 can be accepted because the value of tcount > ttable. This means that there is an influence of the Problem Based Learning (PBL) model on the learning outcomes of Manado State Polytechnic accounting students. In addition, based on the n-gain score, the experimental class student learning outcomes are included in the effective category with a score of 78.25%, which means that the application of PBL is effective for increasing learning outcomes in financial accounting courses on learning outcomes